PENGARUH TRUST, SATISFACTION DAN SERVICE QUALITY TERHADAP REPURCHASE INTENTION PADA PRODUK ANTIVIRUS ESET - Sari Hartini (Jurnal Teknik Informatika, 2015)
Abstract— Maintain relationships with customers is one of the company in maintaining the survival of the business processes of the company itself, because at this time the business competition between companies is characterized by agresifan to each of these companies in winning customers every day by way of competing to provide services best to lure their customers, retain existing customers and cultivate new potential customers not to get the customer to leave the company is one of the PR As a company engaged in the sale of antivirus products, Eset certainly also do not want the customers to switch to products other, therefore demands to be the best should be a firm commitment that the ESET antivirus users, how to maintain the trust and customer satisfaction as well as providing good service to the customer or consumer. This study discusses whether the variable trusts, satification and service quality significantly affect the variable repurchase Intention.